The "quasi-stable" lipid shelled microbubble in response to consecutive ultrasound pulses - Thomas, D; Butler, M; Anderson, T; Emmer, M; Vos, H; Borden, M; Stride, E; de Jong, N; Sboros, V (2012)
Controlled microbubble stability upon exposure to consecutive ultrasound exposures is important for increased sensitivity in contrast enhanced ultrasound diagnostics and manipulation for localised drug release. An ultra high-speed camera operating at 13 × 10 6 frames per second is used to show that a physical instability in the encapsulating lipid shell can be promoted by ultrasound, causing loss of shell material that depends on the characteristics of the microbubble motion. This leads to well characterized disruption, and microbubbles follow an irreversible trajectory through the resonance peak, causing the evolution of specific microbubble spectral signatures. © 2012 American Institute of Physics.